Foundations of Educational Management in a Pedagogical Perspective - Iskandar, Ramadhan Attalarik; Yaya Sunarya (al-Afkar, Journal For Islamic Studies, 2024)
This research problem includes five approaches, namely: the foundation of educational management from a pedagogical perspective; goal-oriented educational management; process-based education management; results-oriented educational management; and education management based on Total Quality Management (TQM). This research aims to find out five approaches to these problems and at the same time overcome them by obtaining final results in the research. The research method used in the research is descriptive qualitative with literature review techniques. The overall results of this research include five approaches, namely: the foundations of educational management from a pedagogical perspective including learning theory, curriculum development, guidance, educational management, and evaluation of learning outcomes; a goal-oriented approach includes integration towards achieving educational goals with mission, background, scenarios, resources, and feedback; a process-based approach includes planning, organizing, workforce placement, directing, coordinating, reporting, and funding; a results-oriented approach includes student learning achievements by paying attention to real results such as measurable skills and knowledge; and an approach based on Total Quality Management (TQM) in education includes continuous improvement involving cooperation from all educational institutions with a focus on customer satisfaction and continuous quality improvement through implementation. The conclusions in this research state that the pedagogical perspective has approaches that provide a solid foundation for improving the quality of educational management.